2022
DOI: 10.3390/vaccines10081176
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination Uptake and Hesitancy among Healthcare Workers in Early 2021 at the Start of the COVID-19 Vaccine Rollout in Cape Town, South Africa

Abstract: Vaccination attitudes among healthcare workers (HCWs) predict their level of vaccination uptake and intention to recommend vaccinations to their patients. To our knowledge, no study has been conducted in South Africa to assess hesitancy toward influenza vaccines among HCWs. We adapted a questionnaire developed and validated by Betsch and colleagues and used it to conduct online and face-to-face interviews among HCWs at the start of the COVID-19 vaccine rollout. Multivariate logistic regression was used to asse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
1
10
2
Order By: Relevance
“…Sociodemographic indicators of hesitancy mirror those found in other South African studies [ 19 , 38 , 39 , 40 ], which found that males and the younger cohort were less likely to vaccinate. In our study, doctors and other HCWs displayed higher levels of hesitancy compared to nurses.…”
Section: Discussionsupporting
confidence: 74%
“…Sociodemographic indicators of hesitancy mirror those found in other South African studies [ 19 , 38 , 39 , 40 ], which found that males and the younger cohort were less likely to vaccinate. In our study, doctors and other HCWs displayed higher levels of hesitancy compared to nurses.…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, we found that older nurses were more likely to accept the influenza vaccine than younger nurses. Several studies suggest that older healthcare workers are significantly associated with higher influenza vaccine uptake and willingness compared to younger age groups, even during the COVID-19 pandemic [ 22 , 54 , 55 , 56 , 57 , 58 ]. This could be explained by old age being an independent predictor of severe complications from influenza virus infections such as pneumonia [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adults (18 years and older), living in these clusters or accessing clinic services in the five study clinics (Senaoane Clinic, Mofolo Community Health Centre, Meadowlands Zone 2 Clinic, Siphumlile Clinic, and Thembelihle Clinic) are deemed eligible for the study. The HDSS communities were included as below (Table 1): (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), sex (male and female) and community (two per cluster). These approaches aim to gather contextual data essential for understanding the factors influencing young people's decisions regarding influenza vaccination, including both motivators and barriers.…”
Section: Samplingmentioning
confidence: 99%
“…C) Qualitative evaluation Additional FGDs, including 10-12 participants per FGD, will be conducted: 8 mid-way through the intervention (during vaccination season) and 8 post-intervention. These FGDs will be mixed gender and will be stratified by age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and community (two per cluster). Key informant interviews (KII) (n=20) with key influencers including, religious leaders, traditional healers and youth leaders, as well as other influencers that may identified through community engagement and communications activities.…”
Section: Samplingmentioning
confidence: 99%